2002
DOI: 10.1590/s1516-31802002000300007
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneoscopic adrenalectomy in an infant with adrenocortical virilizing tumor

Abstract: We performed the first laparoscopic resection using retroperitoneal access for the treatment of an adrenocortical virilizing tumor in a pediatric patient. We believe that retroperitoneoscopic access is a viable and promising option for the treatment of adrenal tumors in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…8 Ciftci et al reported four cases of recurrence after complete surgical resection. 12 Laparoscopic adrenalectomy enables complete resection of both benign and malignant adrenal masses, 1,13,14 and provides good results. Lopes et al treated nine children with adrenocortical tumor via laparoscopic adrenalectomy, with no perioperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…8 Ciftci et al reported four cases of recurrence after complete surgical resection. 12 Laparoscopic adrenalectomy enables complete resection of both benign and malignant adrenal masses, 1,13,14 and provides good results. Lopes et al treated nine children with adrenocortical tumor via laparoscopic adrenalectomy, with no perioperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Studying the overall surgical experiences of the three groups, general surgeons typically use a transperitoneal approach, sometimes with the patient supine; urologists, who typically have more anatomical experience in the retroperitoneal space, use both approaches. Although feasible [25] the retroperitoneoscopic approach in the paediatric patient represents a somewhat demanding access to the adrenal gland because of the very limited working space in young patients. To have an optimal surgical area and adequate working space the vast majority of surgeons prefer the transperitoneal approach for LA in paediatric patients.…”
Section: Different Approaches For Different Surgeons?mentioning
confidence: 99%
“…However, the initial application of extraperitoneal videoendoscopic surgery presents greater technical difficulty, mainly due to a smaller working space, lower lightning and the spatial orientation, which are responsible for a larger learning curve (6)(7)(8). The issue of working space is relative and directly associated with a good peritoneal detachment and proper installation of the ports, being feasible even in children (17,18). Concerning the spatial orientation, the optics must be always kept in a position where it is possible to observe the posterior muscles in horizontal position, thus allowing anatomical parameters to be identified.…”
Section: Commentsmentioning
confidence: 99%
“…We believe that the expansion of the extraperitoneal space with the aid of the atraumatic balloon -either hand-made, industrialized, direct viewing-guided or not -is recommendable since it enlarges the surgical field in areas that cannot be reached by the finger, reducing the need of forceps dissection (3,14,17). The use of the balloon trocar has the advantage of allowing the visualization of structures, especially the renal pedicle, during the expansion.…”
Section: Commentsmentioning
confidence: 99%